Autonomous Continuation of Community Health Workers' Activities in Thegon Township, Bago Region, Myanmar - Oguma, Taeko; Watanabe, Etsuko; Mori, Tomoari; Fujino, Yasuyuki (Frontiers in Public Health, 2020)
Background: Few studies have reported on the autonomous continuation of Community Health Worker (CHW) activities after external supervision and support have ended. Objective: The study reports CHW activity continuation in Thegon Township, Bago Region, Myanmar, observed after the supervision by the external organization is completed. Method: Following the completion of a child nutrition program in Thegon Township, CHWs were left unsupervised and uninformed of a follow-up at 10, 23, and 40 months from the end of the program survey due to unforeseen circumstances. In a follow-up survey in 2014, data on the activity implementation status from CHWs and activity attendance from caregivers of the target children were collected. Focus group discussions were held with caregivers concerning their information sources on child nutrition and health. Results: On average, CHWs were found to have continued with 2.6 of the four core activities, often with modifications, irrespective of the time since completion of the non-profit-organization-led program. Meanwhile, caregiver attendance decreased over time. Caregivers recognized CHWs as information sources. Discussion: Although unsupervised, CHWs ambitiously continued with their activities, but sorted through and modified them, which may have been unrelated to the local acceptance of the program, as caregiver attendance decreased even as CHWs continued the activities. The observation may highlight the importance of proactive engagement and thus, the autonomy of CHWs in their activity continuation.